Nine approximations of modern fertilizer system of agricultural crops - Miroshnichenko, M.M.; Hladkikh, E.Yu.; Revtie-Uvarova, A.V.; Panasenko, E.V.; Zvonar, A.M.; Sorokotiaga, G.V.; Kovalenko, S.S.; Smichenko, V.M. (AgroChemistry and Soil Science, 2018)
The problem of increasing the rates of use of nutrient elements from fertilizers and approaching the maximum possible payback of the fertilizer system with the crop has been raised, taking into account all the factors influencing these indicators. The main objective was to substantiate the feasibility of further consistent fertilization system approximation to the real needs of each cultivated plant. The necessity of taking into account modern breeding genetic achievements and specific nutritional characteristics is shown in the development of fertilizer systems, namely, the balance of nutrients, in order to realize the potential of varieties and hybrids more fully. However, the complexity and inadequate accuracy of the methods of plant nutrition diagnostics remains problematic, in order to solve the problem effectively, the use of functional plant diagnostics is proposed. The emphasis is on taking into account the hydrothermal conditions of the year when adjusting the norms and methods of fertilizing, the depth of their earnings, combining with stress-protectors and growth stimulators to achieve high yields. Finally, it is indicated an important role in economic strategy of farms for expediency of the maximum possible payback of fertilizer systems and ways to achieve optimization of profitability and return on costs.